The Vlasov Maxwell Einstein Equations and its Cosmological Applications (Global Journal of Science Frontier Research, 2019)
The Vlasov-Maxwell-Einstein equations are derived from classical action of Lorentz-Schwarzschild-Hilbert-Einstein. We need and get synchronization of times of different particles. On the basis of obtained results we analyze Einstein's Lambda-term and its connection with dark energy.
Keywords: einstein lambda–term; vlasov–type equation; vlasov–einstein equation; synchronization of times; dark energy